Dry needling: a literature review with implications for clinical practice guidelines1. (August 2014) - Dunning, James; Butts, Raymond; Mourad, Firas; Young, Ian; Flannagan, Sean; Perreault, Thomas
Abstract : Background: Wet needling uses hollow-bore needles to deliver corticosteroids, anesthetics, sclerosants, botulinum toxins, or other agents. In contrast, dry needling requires the insertion of thin monofilament needles, as used in the practice of acupuncture, without the use of injectate into muscles, ligaments, tendons, subcutaneous fascia, and scar tissue. Dry needles may also be inserted in the vicinity of peripheral nerves and/or neurovascular bundles in order to manage a variety of neuromusculoskeletal pain syndromes. Nevertheless, some position statements by several US State Boards of Physical Therapy have narrowly defined dry needling as an 'intramuscular' procedure involving the isolated treatment of 'myofascial trigger points' (MTrPs). Objectives: To operationalize an appropriate definition for dry needling based on the existing literature and to further investigate the optimal frequency, duration, and intensity of dry needling for both spinal and extremity neuromusculoskeletal conditions. Major findings: According to recent findings in the literature, the needle tip touches, taps, or pricks tiny nerve endings or neural tissue (i.e. 'sensitive loci' or 'nociceptors') when it is inserted into a MTrP. To date, there is a paucity of high-quality evidence to underpin the use of direct dry needling into MTrPs for the purpose of short and long-term pain and disability reduction in patients with musculoskeletal pain syndromes. Furthermore, there is a lack of robust evidence validating the clinical diagnostic criteria for trigger point identification or diagnosis. High-quality studies have also demonstrated that manual examination for the identification and localization of a trigger point is neither valid nor reliable between-examiners. Conclusions: Several studies have demonstrated immediate or short-term improvements in pain and/or disability by targeting trigger points (TrPs) using in-and-out techniques such as 'pistoning' or 'sparrow pecking'; however, to date, no high-quality, long-term trials supporting in-and-out needling techniques at exclusively muscular TrPs exist, and the practice should therefore be questioned. The insertion of dry needles into asymptomatic body areas proximal and/or distal to the primary source of pain is supported by the myofascial pain syndrome literature. Physical therapists should not ignore the findings of the Western or biomedical 'acupuncture' literature that have used the very same 'dry needles' to treat patients with a variety of neuromusculoskeletal conditions in numerous, large scale randomized controlled trials. Although the optimal frequency, duration, and intensity of dry needling has yet to be determined for many neuromusculoskeletal conditions, the vast majority of dry needling randomized controlled trials have manually stimulated the needles and left them in situ for between 10 and 30 minute durations. Position statements and clinical practice guidelines for dry needling should be based on the best available literature, not a single paradigm or school of thought; therefore, physical therapy associations and state boards of physical therapy should consider broadening the definition of dry needling to encompass the stimulation of neural, muscular, and connective tissues, not just 'TrPs'.